The ANTIBIOTICS SENSITIVITY TEST ON Escherichia coli THAT CAUSE DIARRHEA IN MANADO CITY - Oksfriani Jufri Sumampouw (JCPS (Journal of Current Pharmaceutical Sciences), 2018)
Antibiotics resistance has become an important issue in the health, especially pharmacy. Several types of bacteria have been found that have the ability to resist antibiotics. One type of bacteria was Escerichia coli (E. coli). E. coli was one of the microorganisms that cause diarrhea. The purpose of this study was to determine the sensitivity of antibiotics to E. coli causing diarrhea in the Manado city. This research was an experimental research. This research was located at the Microbiology Laboratory, Faculty of Fisheries and Marine Sciences Sam Ratulangi University. Sensitivity testing using the Well method. The results showed that at a dose of 0.1 ppm all antibiotics could inhibit bacterial growth. Resistance begins to occur at the concentration of antibiotics of 0.001 ppm. The conclusion of this study was that E. coli has the ability to resist the Chlorampenicol, Ampicillin, Amoxicillin, and Tetracyclin. In contrast to Ciprofloxacin resistance has not been found.